Ultrasound elastography: A new tool in pulmonology - Maria Morales-Gonzalez; Aurelio Arnedillo (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2019)
Lung cancer continues being a serious cause of death in developed countries with an increase in its incidence in recent years. According to the above, it is not uncommon to think that new techniques are being investigated to facilitate diagnosis, as well as its staging.